2014
DOI: 10.2478/geoca-2014-0022
|View full text |Cite
|
Sign up to set email alerts
|

Petrology and geochemistry of a peridotite body in Central- Carpathian Paleogene sediments (Sedlice, eastern Slovakia)

Abstract: Abstract:We studied representative samples from a peridotite body situated NE of Sedlice village within the CentralCarpathian Paleogene sediments in the Central Western Carpathians. The relationship of the peridotite to the surrounding Paleogene sediments is not clear. The fractures of the brecciated peridotite margin are healed with secondary magnesite and calcite. On the basis of the presented bulk-rock and electron microprobe data, the wt. % amounts of mineral phases were calculated. Most of calculated "mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
(16 reference statements)
0
5
0
Order By: Relevance
“…The abyssal type harzburgites in the Jaklovce Unit ophiolite complex, having a character of weakly depleted harzburgites are consistent with the marginal basin with the subduction-unrelated mantle rocks [7,[90][91][92][93][94]. They are also typical of the mantle portion of the ophiolitic complexes [93,94] from the passive margins reported by [129], and which evolved during rift-drift and seafloor spreading [130].…”
Section: Geochemical Constraints On the Meliatic Basalts Paleotectonimentioning
confidence: 55%
See 2 more Smart Citations
“…The abyssal type harzburgites in the Jaklovce Unit ophiolite complex, having a character of weakly depleted harzburgites are consistent with the marginal basin with the subduction-unrelated mantle rocks [7,[90][91][92][93][94]. They are also typical of the mantle portion of the ophiolitic complexes [93,94] from the passive margins reported by [129], and which evolved during rift-drift and seafloor spreading [130].…”
Section: Geochemical Constraints On the Meliatic Basalts Paleotectonimentioning
confidence: 55%
“…(2) Oceanic margin crust; composed of the Middle (Ladinian) to Upper Triassic (Carnian-Norian and younger) pelagic cherty sediments, N-MORBs and rare alkaline OIBs associated with serpentinized and rodingitized, mostly harzburgitic, mantle fragments (cf. [2,4,7,8,77,[90][91][92]).…”
Section: Mélange Sources As Indicators Of the Meliatic Triassic-jurasmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have demonstrated that the Cr # values of spinels have a covariant relationship with the degree of melt extraction of mantle peridotites (e.g., Hellebrand, Snow, Dick, & Hofmann, 2001;Koppa, Koller, & Putiš, 2014;Liu et al, 2012). To calculate the extent of melting (F), Hellebrand et al (2001) proposed a logarithmic equation in terms of spinel Cr # values from 0.10 to 0.60:…”
Section: Degrees Of Partial Melting: Implications For Multiple Episodes Of Melt Extractionsmentioning
confidence: 99%
“…The Jaklovce Unit (Figure 5) is the most characteristic oceanic or ophiolitic sedimentary-magmatic succession of the Meliaticum composed of pelagic cherty sediments to radiolarites, N-MORBs and rare alkaline OIBs associated with serpentinised and rodingitised, mostly abyssal harzburgitic, mantle fragments [9,11,14,15,53,[60][61][62]. The oceanic Jaklovce Succession was more precisely defined using our new biostratigraphic data from radiolarites and cherty carbonates which distinguished the Lower (Ladinian), Middle, and Upper (Carnian to Norian?)…”
Section: Lithostratigraphy and Geochemistrymentioning
confidence: 99%